2023
DOI: 10.1108/ijebr-06-2022-0548
|View full text |Cite
|
Sign up to set email alerts
|

Low-income logics: institutions' varying impact on entrepreneurship

Abstract: PurposeThe authors address the role that income plays in allowing individuals to resist dominant institutional norms and engage in entrepreneurship.Design/methodology/approachThis is a conceptual article that develops propositions about the relationship of institutional logics and income level with opportunity entrepreneurship.FindingsThe authors suggest that high-income individuals are less impacted than low-income individuals by institutional logics that do not support opportunity entrepreneurship. More spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…This can serve as the primary strategy for firms to mitigate the negative impact on their entrepreneurial behavior (Kryeziu et al , 2022b). Another area worth exploring is the potential connection between our study and the research conducted by Smith and Lanivich (2023). They found that a national business system reflecting market logic tends to stimulate opportunity entrepreneurship among individuals with lower incomes, which could potentially extend to the entrepreneurs in our study presumed to have higher incomes.…”
Section: Implications and Conclusionmentioning
confidence: 74%
“…This can serve as the primary strategy for firms to mitigate the negative impact on their entrepreneurial behavior (Kryeziu et al , 2022b). Another area worth exploring is the potential connection between our study and the research conducted by Smith and Lanivich (2023). They found that a national business system reflecting market logic tends to stimulate opportunity entrepreneurship among individuals with lower incomes, which could potentially extend to the entrepreneurs in our study presumed to have higher incomes.…”
Section: Implications and Conclusionmentioning
confidence: 74%
“…These policies and initiatives can give entrepreneurs rights to protect their property, investments and competitive advantages. Conversely, overly bureaucratic licensing requirements, high cost of legal settlements and a lack of protection for property rights, can create regulatory challenges for entrepreneurs (Abor and Quartey, 2010; Smith and Lanivich, 2023).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Notably, China's commitment to research and development (R&D) has been substantial, with an investment of 2.45 tn Chinese Yuan (CNY) in 2020, positioning it as the second-largest R&D investors in the world (Jiang et al, 2020). In light of the Life-cycle approach, USPs can provide essential resources throughout the entire process of revenue generation (Drori et al, 2009;Smith and Lanivich, 2023). This includes not only incubation funding but also USPs size, which is predominantly driven by human capital.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the Life-cycle approach, USPs can provide essential resources throughout the entire process of revenue generation (Drori et al. , 2009; Smith and Lanivich, 2023). This includes not only incubation funding but also USPs size, which is predominantly driven by human capital.…”
Section: Introductionmentioning
confidence: 99%